OPTIMALISASI POTENSI PESERTA DIDIK MELALUI PEMETAAN GAYA BELAJAR BERBASIS KECERDASAN MAJEMUK PERSPEKTIF ISLAM - Irmayanti, Azizah Putri; Deliani, Nurfarida; Batubara, Juliana; Syamsi, Syamsi; Maulana, Febrian (Ibn Khaldun University, Bogor, 2024)
This article aims to describe the concept of mapping learning styles of students based on multiple intelligences in order to improve academic achievement based on the principles of Islamic education. Based on the principles of Islamic education. Research shows that every learners have different levels of intelligence and learning styles. Mapping the profile of learners based on their intelligence and learning style is important to facilitate the development of academic potential. Is important to do in order to facilitate the development of their academic potential potential optimally. The literature review method was used to review literature related to the topic. The results show that the application of mapping of learning styles and multiple intelligences is in line with the concept of holistic and humanist education in Islam. Holistic and humanist education concepts in Islam. The relevance of the findings is also supported by the example of the Prophet Muhammad in educating the companions. Conclusion, optimization of academic achievement can be achieved through learning style mapping and adjusting learning strategies to the adjustment of learning strategies with multiple intelligence profiles profile of each learner. Through the integration of this concept, it is expected to improve the effectiveness of education by accommodating individual differences learner's individual differences in more depth, while enriching the learner's learning experience spiritually and intellectually. learning experience spiritually and intellectually.